Land Tax - Rodrigo, Luis Carlos (1968)
This paper addresses the figure of the land tax focused on its social-economic transcendence. The author argues that this is an extra-fiscal resource of social order that can be used as an instrument of agrarian reform. In this sense, the use of this tax should not be considered as an addition to existing taxes, but as part of an organic tax system that does not discourage real estate investment. The author presents the historical development of the land tax, its characteristics and justification; he also distinguishes this figure from the estate tax and the capital tax. Finally, he analyzes the Peruvian draft laws that deal with the land tax and presents his conclusions based on the study carried out on this figure and the existing legislative projects.